The Distributional Impacts of Early Employment Losses from COVID-19 - Seung Jin Cho; John V. Winters (Global Labor Organization (GLO), 2020)
COVID-19 substantially decreased employment, but the effects vary among demographic and socioeconomic groups. We document the employment losses in April 2020 across various groups using the U.S. Current Population Survey. The unemployment rate understates employment losses. We focus on the percentage of the civilian population that is employed and at work. Young persons experienced the largest employment losses. Individuals with less education and lower family income experienced much larger employment losses than their more educated and higher income counterparts. Hispanics and blacks were more adversely affected than whites.
Keywords: I1; J1; J2; 330; COVID-19; coronavirus; pandemic; employment; job losses